The Relationships between Urban Form and Travel Patterns. An International Review and Evaluation - Stead, Dominic; Marshall, Stephen (European Journal of Transport and Infrastructure Research, 2001)
There is a growing body of research concerned with the relationship between urban form and travel patterns. Studies originate from a diversity of sources, and encompass a variety of geographic scales and locations. To add to this diversity, many different characteristics of urban form to have been examined in these studies, and travel patterns have been measured in a number of different ways. This paper brings together in a systematic way the results of many recent studies on urban form and travel patterns over the last 20 years. As well as this systematic approach, other key aspects of this review paper include the identification of where research has been concentrated (and where there are gaps in research), and in the critique of the studies, which includes issues of data accuracy, reliability and quality, the applicability of research methods and data interpretation. The critique focuses in some detail on the interaction of socio-economic factors with urban form and travel patterns.